Pengembangan Strategi Bisnis Tas Handmade Pada CV Cagho Prima Nusantara - Luthfi, Zulfan; Wijaya, Fanji (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
The purpose of this study is to examine and analyze the development of the business strategy of CV Prima Nusantara, a company that focuses on the production of handmade bag. Handmade bag industry has emerged as a key player in the fashion industry, attracting consumers seeking unique and affordable goods. Using the SWOT analysis method, this study examines the internal factors (Strengths and Weaknesses) and external factors (Opportunities and Threats) that affect the CV of the Primary Care Physician of Nusantara. When production costs and capacity are reduced to an extreme, design creativity, day-to-day design, and product quality become the most important factors. It is anticipated that CV Cagho Prima Nusantara will be able to develop innovative and flexible business strategies to maximize market share and train personnel. A SWOT analysis will be conducted to assist CV Cagho Prima Nusantara in maximizing internal resources, overcoming obstacles, and maximizing opportunities.